The Associations Between Depression, Regular Exercises, and Falls Among the CommunityDwelling Older People - Li Fang; Ching-Lin Fang; Shu-Hui Fang (AVES, 2024)
AIM: The aim of this study was to explore the relationship between regular exercise, depression, and fall among the community older people to find out the predictors of fall. METHODS: This study applied cross-sectional and correlational study design. The study recruited 285 community older people by using the questionnaires which included social-demographic data, regular exercise, depression, and whether fall history questionnaires were used in this study. RESULTS: The mean score of the depression scale for older people was 3.47 (SD 2.92). People who took anti-hypertensive or anti-diabetes drugs have higher risks of falls than those who did not (B = 1.659; p < .001; Exp (B) = 5.256). Community-dwelling older people with regular exercise have a lower risk of falls than those without (B = −1.485; p < .001; Exp(B) = 0.227). CONCLUSION: Rehabilitation programs designed to improve both the older people's physical function and mental health played very important roles in preventing falls. It is necessary to undergo depression screening programs for the community older people in order to detect older people depression in advance and prevent the incidence of falls.